Pueblos mágicos y nuevas ruralidades. El caso de Álamos, Sonora - Rascón, Cristina Marínez (Diálogos Latinoamericanos, 2013)
The Mexican town, Alamos in Sonora has specific urban and rural characteristics that are central in the national Mexican tourism policy program “Magic Villages”. This program is related to the local development and the redesign of touristic cities. The approach of the New Ruralities allows identifying the processes of socio-spatial transformation of these centers and also the role of the productive sectors. The services for the rural sector, led by the means of governmental plans and programs, are reflected in the everyday life, before and after the Magic Town Program; operative bureaus, commerce and general services are evidence of this transformation. Also, the recent operation of two mines reactivates the local economy through the generation of direct and indirect jobs. In summary, before being a Magic Town, Alamos was already a touristic city and yet, the center of one of the most poor municipalities of the state.